KEPEMIMPINAN DAN IMPLEMENTASINYA PERSPEKTIF AL-QURAN - Muhammad Rizqi (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2017)
This research is purposed to study leadership in al-Quran. The article is discussed popular topics in the study of al-Quran and Interpretation. It is caused by many terminologies used for leaders in al-Quran in which each of them applied have different stressing. Several terms applied in al-Quran are to explain about leaders in this research are khalifah, ulul-amr, malik, and Al-Imam/Imamah. Khalifah is used for leaders as the first human which replace the leadership of Allah’s creatures in the past. Al-Malik is used for leaders at certain dynasties after periods of Khalifah. Ulil Amri is used for the leader who is loyal to Allah and His prophets in government. Al-Imam or Imamah is used for the leader with having an emphasis on therejection of cruelty. At return, it becomes a model, and messanger of kindness. Therefore, he must govern the country in justice and rightness, forbid any crimes. Some criteria of a good leader can become a model, recommender of kindness, Amar ma`rûf nahy mungkar, believable, as well as the implementation of duties as Moslems.